Automated production processes in the rotor blade industry – Solutions for a continuous direct textile layup. Issue 11 (14th November 2019) - Franke, J.; Ohlendorf, J.‐H.; Thoben, K.‐D.
Abstract: Recent efforts concerning the automation of production processes for wind turbine rotor blades involve several new challenges. The technical fabrics used present specific features in handling due to their limp characteristics. Because of the steady growth of modern offshore wind turbine dimensions, larger rotor blade mold surfaces have to be covered with technical fabrics which influence the size and the weight of the handling systems used for automation. For an economic production of future wind turbine types, an increase in efficiency – by shortening the process cycle times – is crucial. Consequently, the time‐consuming process steps need to be automated. The article focuses on the continuous direct textile layup process and delivers ideas and solutions for the resulting challenges of process steps like storing, cutting and draping a technical textile in an automated rotor blade production. Translation abstract: Die aktuellen Bestrebungen zur Automatisierung der Rotorblattproduktion für Windenergieanlagen bringen einige neue Herausforderungen mit sich. Die eingesetzten technischen Textilien weisen durch ihr biegeweiches Materialverhalten Besonderheiten im Handhabungsprozess auf. Weiterhin sind durch die stetig wachsenden Abmessungen moderner Offshore‐Windenergieanlagen immer größere Rotorblattformoberflächen mit technischem Textil zu belegen, was auch die Größe und das Gewicht der eingesetzten Handhabungssysteme beeinflusst. Für eine wirtschaftliche Produktion der zukünftigen Windenergieanlagentypen ist daher eine Effizienzsteigerung durch verkürzte Prozesszykluszeiten unabdingbar. Daher sollen die zeitintensiven Prozessschritte automatisiert werden. Der Artikel konzentriert sich auf den kontinuierlichen Direktablageprozess technischer Textilien und liefert Ideen und Lösungen für die resultierenden Herausforderungen von Prozessschritten wie Speichern, Schneiden und Drapieren eines technischen Textils in einer automatisierten Rotorblattproduktion.